Application of immunophenotypic analysis in distinguishing chronic myelomonocytic leukemia from reactive monocytosis. Issue 6 (17th October 2018) - Feng, Ru; Bhatt, Vijaya Raj; Fu, Kai; Pirruccello, Samuel; Yuan, Ji
Abstract : Objectives: The purpose of this study was to determine whether immunophenotypic profiles detected by flow cytometry are useful in differentiating chronic myelomonocytic leukemia (CMML) from reactive monocytosis, and between CMML subtypes. Methods: Eight‐color flow cytometry was used to immunophenotype blasts, monocytes, and granulocytes in the bone marrow of 34 patients with CMML and 12 patients with reactive monocytosis. Results: Bone marrow myeloblast, promonocyte, and monocyte counts by flow cytometry were significantly higher in the CMML group than in the reactive monocytosis group. Myeloblast aberrancies were present in all CMML patients as compared with 2 of 12 (16.7%) reactive monocytosis patients ( P < 0.001). The number of blast aberrancies ranged from one to nine (median, four) in CMML patients and 94.1% of CMML cases exhibited ≥ two aberrancies. In contrast, two reactive monocytosis cases showed only one phenotypic abnormality of blasts. Monocyte and granulocyte aberrancies were present in 26 of 34 (76.5%) and in 31 of 34 (91.2%) CMML patients, respectively. Decreased side scatter (SSC) and abnormal CD11b/CD13/CD16 maturation pattern in granulocytes were more frequent in CMML than in reactive monocytosis. No significant differences in antigen expression were detected between the CMML subtypes except that altered CD45/SSC pattern on the blasts was more commonly observed in CMML‐0/1 than in CMML‐2. Conclusions: CMML has phenotypic aberrancies in monocytes, granulocytes, and more frequently in myeloblasts. Aberrant expression of two or more antigens in myeloblasts by flow cytometry has a high sensitivity (94.1%) and a high specificity (100%) to differentiate CMML from reactive monocytosis. © 2018 International Clinical Cytometry Society